Application of Biopesticide from Eucalyptus grandis on Mortality of Fruit Flies (Bactrocera sp.) on Sweet Citrus (Citrus X Sinensis) Plants - Taufik, Muhammad; Zuhra, Cut Fatimah; Cahyady, Boby; Hardiyanti, Rini; Ardilla, Desi; Razali, Mariany; Alfian, Zul (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The application of biopesticides is one of the safest alternatives to realize organic agriculture that does not cause harmful impacts to both consumers and the environment. This activity aims to apply biopesticides in eradicating fruit flies (Bactrocera sp.) on Sweet Orange (Citrus X Sinensis) plants. The partner location is the Bukit Rumah Sendi Farmers Group in Karo Regency. Eucalyptus grandis leaves were extracted using steam distillation then the concentration of 1,8 Sineol was determined using GCMS and the concentration was 52%. Eucalyptus oil was mixed with kerosene and detergent then determined the LC50 value in fruit flies and observed for 24, 48, 72, and 96 hours and produced an LC50 value of 35%. This shows that biopesticides are quite effective in eradicating fruit flies.